Experimental Investigation of the Reynolds Shear Stress Exceedance Rate for the Injury and Disorientation Biocriteria Boundary in the Pool-Orifice and Vertical Slot Type Fishways - Gordon Gilja; Eva Ocvirk; Robert Fliszar (Applied Sciences, 2021)
Fragmentation of rivers has a negative impact on river’s ecological status which can be improved by the construction of fishways next to obstacles in rivers that prevent a free migration. Flow field characteristics are key factors in the design process of hydraulically efficient fishways—flow and turbulence patterns in a functional fishway allow fish to enter, progress through and exit with minimum time/energy expenditure. The aim of this paper is an experimental study of the flow field characteristics measured in the physical fishway model with the goal of providing information on the Reynold’s shear stress distribution that would facilitate their design in accordance with the environmental requirements. The focus of the research was on the nominally hydraulically efficient con-figuration pool-type fishways—pool-orifice and vertical slot. Fishway geometry was varied for bottom slope (7.5%, 10% and 12.5%), pool length (45 cm, 60 cm and 90 cm) and orifice size (8 × 8 cm, 10 × 10 cm and 12 × 12 cm) in a model scaled 1:3 to the prototype. Since Reynold’s shear stress has been identified as the main turbulent parameter affecting fish swimming performance and behavior, it is used as the basis for the analyses. The velocity data were collected with Vectrino ADV and processed in all three planes—streamwise, horizontal and vertical. Reynold’s shear stress data were analyzed according to the injury (>50 N/m2) and disorientation (>30 N/m2) biocriteria boundaries defined in the literature. The percentage of the flow field exceeding the boundaries were analyzed depending on the fishway geometry. The results obtained in this research suggest that the critical design parameter is the orifice size for the pool-orifice fishways and the pool length for the VS fishway. The Reynold’s shear stress is generally the highest in the bottom layer for pool-orifice fishways and the surface layer for vertical slot fishways.